Analysis of causes and clinical pattern of infertility in couples coming to a tertiary care centre in Bihar, India - Singh, Kalpana; Kumari, Rekha; Ranjan, Alok; Bharti, Geetam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Infertility is one of the major health problems and a socially destabilizing condition for couples often causing marital disharmony. Infertility is defined as the failure to achieve a clinical pregnancy after 12 months or more of regular unprotected sexual intercourse. Worldwide, its prevalence is approximately 8-12%.There are numerous factors such as anatomical, physiological and genetic factors that cause infertility. Many environmental and acquired factors also lead to inability to conceive. Objective of the present study was to determine the causes and clinical pattern of infertility in infertile couples. Methods: It was a hospital based observational study carried out on 750 women in reproductive age group attending out-patient clinic of Reproductive Biology Department of Indira Gandhi Institute of Medical Sciences (IGIMS) at Patna during April 2013 to March 2017. All the cases of primary and secondary infertility diagnosed after full examinations and laboratory tests were included and cases lacking of full examinations and laboratory tests were excluded. All the data of infertile couples were recorded in a semi-structured Case Information Performa. Results: Out of 750 women 454 women had all the data and they participated in the study Nearly 68% women had primary infertility and rest had secondary infertility. Male factor was responsible in 37.39%, female factor in 20.48%, unexplained in 22.46% while a combination of both factor was seen in 8.37% cases in our study .135 women had irregular menstrual cycles in which 64(47%) had oligomenohhrea. 79% women had normal ultrasonography and nearly 11% of women had evidence of PCOD. 24% women had hypothyroidism (TSH more than 4.5 IU/L) and 59(13%) were found to have high level of prolactin i.e. >25 ng/ml. Nearly 8% of women had high level of FSH i.e. more than 10 IU/L which is an indicator of ovarian resistance. In nearly 16% women one fallopian tube was found blocked and 8% had both tubes blocked in hysterosalpingography. Husband semen analysis was done to assess male factor. Nearly 14% of their male partners suffered from azoospermia and 23% had at least one abnormal parameter in semen analysis. Conclusions: Etiological pattern of infertility varies in different parts of World. Male and female factors both are responsible for infertility. So, both the partners should be counselled and investigated properly.